2020
DOI: 10.7150/jca.42734
|View full text |Cite
|
Sign up to set email alerts
|

MiRNAs in Radiotherapy Resistance of Nasopharyngeal Carcinoma

Abstract: Nasopharyngeal carcinoma (NPC) is one of the most common malignant tumors of the head and neck in Southeast Asia and southern China. Although the comprehensive treatment based on intensity-modulated radiation therapy improves outcomes, the five-year survival rate of NPC patients is low, and the recurrence remains high. Radiotherapy resistance is the main cause of poor prognosis in NPC patients. MicroRNAs (miRNAs) are a class of endogenous non-coding RNAs regulating various biological functions in eukaryotes. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 97 publications
0
19
0
Order By: Relevance
“…They are confirmed as vital gene modulators and work through complementary pairing with the 3′-untranslated regions (UTRs) of their target genes, ultimately triggering mRNA degradation or reducing translation ( 17 ). Numerous miRNAs are abnormally expressed in NPC and are essential in inducing malignancy and tumorigenesis ( 18 20 ). The theory of competitive endogenous RNA (ceRNA) proposed by Salmena et al ( 21 ) has accelerated research on lncRNA mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…They are confirmed as vital gene modulators and work through complementary pairing with the 3′-untranslated regions (UTRs) of their target genes, ultimately triggering mRNA degradation or reducing translation ( 17 ). Numerous miRNAs are abnormally expressed in NPC and are essential in inducing malignancy and tumorigenesis ( 18 20 ). The theory of competitive endogenous RNA (ceRNA) proposed by Salmena et al ( 21 ) has accelerated research on lncRNA mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Through the intersections of three prediction databases (Targets can, miRanda and miRDB), miR‐545‐3p was selected as the target of lncRNA XIST. microRNAs are involved in multiple biological processes, including cellular differentiation, proliferation, and apoptosis 34,35 . Previous studies have demonstrated that miR‐545‐3p affects the pathogenesis of various cancers 36–38 .…”
Section: Discussionmentioning
confidence: 99%
“…Translationally, this study demonstrates the clinical potential of MET inhibitors for increasing radiosensitivity in CSCs which could be applied to HNSCC since Crizotinib has shown to inhibit CSC-like populations and impair metastasis in patient-derived xenograft (PDX) HNSCC models [103]. It would be interesting to evaluate if EGFR uses the same signalling cascade identified in this study to drive RR; this could be exploited with anticancer combinational therapies in HNSCC involving cotargeting c-MET and EGFR, given that EGFR is frequently overexpressed in HNSCC, and is demonstrated to activate DNA repair [108,109].…”
Section: Targeting the Central Component Of Hr -Rad51mentioning
confidence: 95%